An Intraarticular Osteoid Osteoma: A Case Report & Review of Literature - Pant, AR; Gupta, MK; Santhalia, PK; Ahmad, K; Kalawar, RPS; Rauniyar, RK (Nepalese Journal of Radiology, 2014)
Osteoid osteoma (OO) is one of the common benign bone tumors but an uncommon cause of musculoskeletal pain. Its diagnosis is usually not difficult in classic clinical setup and in typical location in diaphyseal region. However, the diagnosis of juxta or intraarticular osteoid osteoma (IAOO) is challenging because of atypical clinical presentation responsible for delay in diagnosis and treatment. We report a rare case of IAOO as a cause of chronic shoulder pain to make clinician aware to help in its early diagnosis and management. A 28-year-old woman presented with chronic debilitating right shoulder pain. The diagnosis was established on CTscan after 2 years of onset of symptoms because of atypical clinical presentation as a chronic monoarthritis of the shoulder. CTscan demonstrated radiolucent nidus with central calcification with areas of surrounding sclerosis. The tumor was excised surgically and histopathologic examination confirmed the diagnosis of osteoid osteoma. So, in the scenario of an unexplained chronic monoarthritis, the possibility of intraarticular osteoid osteoma should also be kept in mind. CT-scan remains the investigation of choice for demonstrating the nidus and surgical exicision relieves the symptoms. DOI: http://dx.doi.org/10.3126/njr.v3i2.9615 Nepalese Journal of Radiology Vol.3(2)July-Dec, 2013: 77-80